Determination of the dynamic hardness of greases as a characteristic of deformation properties in a tribocontact - Dykha, O.; Staryi, A.; Dytyniuk, V.; Dykha, M. (Problems of Tribology, 2022)
The efficiency of plastic oil is determined by the duration of its retention on the surface. Evaluation of the effectiveness of plastic lubricants depends on their mechanical properties. It is proposed to use the dependence of hardness on time when pressing a spherical indenter as one of the basic characteristics of the mechanical properties of plastic oils. The method of determining the function of oil hardness is based on the mechanics of contact interaction of a solid ball and a plane presented in this work, which has the property of creep according to the flow theory. One of the main methods of testing the deformation properties of plastic lubricants is to determine the number of penetrations. The number of oil penetrations is determined by the depth of indentation of the indenter; more informative for such a process is the ultimate pressure (hardness), which actually reflects the phenomenon of resistance to indenter indentation in the material. For uniform distribution of pressure under a spherical indenter the technique of construction of function of dynamic hardness of plastic materials is defined and on the basis of tests results of construction of dynamic hardness are received. Tests on contact creep of plastic lubricants are carried out, functions of dynamic hardness are received and the analysis of influence of character of change of dynamic hardness on wear processes in the presence of lubricants is carried out. To analyze the influence of deformation properties on the tribological properties of lubricants, comparative tests of the two above-mentioned types of lubricants on a four-ball friction device were performed. It was found that Litol-24 oil has the best wear resistance. The nonlinear period of running-in for this oil is practically absent that, obviously, under the given conditions of tests is connected with more stable in time deformation properties.